2011
DOI: 10.1007/s12665-011-1064-2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental geochemistry and quality assessment of mine water of Jharia coalfield, India

Abstract: A long mining history and unscientific exploitation of Jharia coalfield caused many environmental problems including water resource depletion and contamination. A geochemical study of mine water in the Jharia coalfield has been undertaken to assess its quality and suitability for domestic, industrial and irrigation uses. For this purpose, 92 mine water samples collected from different mining areas of Jharia coalfield were analysed for pH, electrical conductivity (EC), major cations (Ca 2? , Mg 2? , Na ? , K ? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…The knowledge of hydrochemistry is essential to determine the origin of chemical composition of groundwater (Zaporozec, 1972). The hydrogeochemical evaluation study is becoming very important to determine the processes involved in the chemical evolution of groundwater (Andrade and Stigter, 2011;Singh et al, 2012a). People also mostly depend upon the groundwater as the water resource for all the activities like drinking, agriculture and domestic use.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of hydrochemistry is essential to determine the origin of chemical composition of groundwater (Zaporozec, 1972). The hydrogeochemical evaluation study is becoming very important to determine the processes involved in the chemical evolution of groundwater (Andrade and Stigter, 2011;Singh et al, 2012a). People also mostly depend upon the groundwater as the water resource for all the activities like drinking, agriculture and domestic use.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, considering the expected lack of water supply in the future [34], the removed water may then become a potential resource for agricultural utilization. In fact, agricultural irrigation using such industrial waste water had been reported elsewhere [35]. …”
Section: Possible Application Of the Dimethyl Ether Extraction Methodmentioning
confidence: 99%
“…The RCF also contains large reserves of iron ore occurring chiefly as nodules along with good quality fire clay in the Barakar stage of RCF (Sikdari et al 2004). The high demand for coal from this area has ensued in intensive mining activities and expansion of the lease hold areas, along with the piling up of vast areas of overburden material and tailings, thus resulted in significant long-term environment hazards in the form of acid mine drainage and contamination of local water resources with toxic trace metals (Singh and Singh 2010;Banerjee 2011;Singh et al 2012). …”
Section: Methodsmentioning
confidence: 99%